Design of Dual Band Stacked RDRA for 5G Applications - A. I. Bugaje; M. H. Jamaluddin; R. Selvaraju; M. N. Hafiz; AdulKadir Bello Shallah (Universitas Ahmad Dahlan, 2018)
This paper focuses on the investigation and discussion of three different designs of stacked Rectangular Dielectric Resonator Antenna (RDRA) at dual bands of 25 GHz and 32 GHz for 5G applications. First, basic stacked RDRA. Second, basic stacked RDRA with a single notch. Third, basic stacked RDRA with double notches. All the proposed structure consists of two stacked DRA of dielectric permittivity of 10 which mounted on a Duriod dielectric substrate of dielectric permittivity of 2.2 and feed by Microstrip aperture slot feeding technique (MSA) for 50 Ω characteristic impedance. Authentication of all the proposed designs comparison is completed using 3D simulation tool by observing the performance of reflection coefficient, bandwidth, and gain. All the proposed RDRA are demonstrated simulated reflection coefficient lower than 20 dB for both bands and simulated gain more than 6 dBi. Meanwhile, for simulated bandwidth, only the proposed basic stacked RDRA with single and double notches are demonstrated simulated bandwidth more than 1 GHz, which fulfill the requirement for 5G applications.